Collective insights on the past, present, and future of restorative justice research - Sliva, Shannon M. (Criminal justice studies, 2025)
In 2022, the National Center on Restorative Justice (NCORJ) launched the Restorative Justice Research Community (RJRC) and selected a cohort of research fellows to engage in a series of dialogues about the state of restorative justice research and its future. Eight dialogues occurred over 2 years. Each was premised on pre-selected questions, supported by pivotal pieces of literature, and guided by a facilitator. This manuscript, co-written by the research fellows, documents and reflects on the key themes and tensions surfacing in their dialogues. It draws from historical artifacts of the dialogue process, including recordings and transcriptions, meeting documents, and personal notes. Emergent themes explored by the fellows include definitional tensions in the field and their effect on the progress of research, the paradoxical desire for and resistance to typologies and measurements of restorative justice processes, and the process of conducting research from a restorative paradigm. The manuscript synthesizes these conversations, identifies areas of congruence or dissonance that developed among the fellows and their broader networks, and includes reflexive observations on how the dialogues influenced the fellows’ thinking in terms of restorative justice research. It concludes with an offering of guiding inquiries to seed future research in the restorative justice field.